Circulating D-Dimers Increase the Risk of Mortality and Venous Thromboembolism in Patients With Lung Cancer: A Systematic Analysis Combined With External Validation - Li, Jing; Yan, Shanle; Zhang, Xiaohui; Xiang, Mengqi; Zhang, Chuanhua; Gu, Ling; Wei, Xiaoying; You, Chuanyun; Chen, Shenhua; Zeng, Daxiong; Jiang, Junhong (Frontiers in Medicine, 2022)
Background: D-dimer is a fibrin-degrading substance that is soluble and whose degradation is produced by plasma protein-mediated degradation of cross-linked fibrin. Previous investigations have shown a link between D-dimer and mortality in lung cancer patients. However, different investigations varied whether D-dimer could predict prognosis in these patients. Methods: A meta-analysis and systematic review of all available cohort studies were performed on the link between circulating D-dimer levels and survival of lung cancer patients. Relevant studies were searched in Embase, Cochrane Library, and PubMed databases. Data from 540 lung cancer patients from the First Hospital of Soochow University and Sichuan Cancer Hospital were used for external validation. Results: We finally obtained 19 eligible cohort studies with pooled HR showing that high D-dimer levels contribute to death in the tumor group (HR 1.62, 95% CI: 1.39-1.88, I2 = 75.0%). Further stratified analysis showed that higher circulating D-dimer in the advanced lung cancer group was linked to a 1.91-fold risk (HR = 2.91, 95% CI: 2.24-3.78, I2 = 6.0%). Incorporation of other variables, including days of follow-up, country, design, public year, population, disease status, and quality score, into the meta-regression model, indicated that disease status was an additional source of heterogeneity (p<0.001). External validation of 540 patients also showed that high levels of D-dimer showed a higher risk of overall mortality (HR 1.39, 95% CI: 1.13-1.72, p-value = 0.002) and VTE events (HR 3.98, 95% CI: 1.99-8.70, p-value = 0.002) in lung cancer patients. Conclusions: High circulating plasma D-dimer levels independently predict long-term prognosis and the risk of venous thromboembolism in lung cancer.